Equal rights to paid parental leave and caring fathers- the case of Iceland - Arnalds, Ásdís A.; Eydal, Guðný Björk; Gíslason, Ingólfur V. (Veftímaritið Stjórnmál og stjórnsýsla, 2013)
In 2000 the Icelandic parliament adopted unanimously a new and radical law on parental leave. The leave was extended from six months to nine; divided between the parents so that fathers were allotted three months, mothers three and the remaining three divided between the two. One reason given for this division was to try to ensure that children received care from both parents. From the results of a questionnaire answered by parents who had their first child in 1997, 2003 or 2009 it was estimated whether the intention of the law was put into practice. The results indicate that the division of care between parents, from birth until three years, has changed in the intended direction and that this is mainly due to the law. The results also showed that this is least common among parents that do not live together. However, even amongst these parents the division of care is more equal among those who had their first child in 2009 than those who had their first in 1997. Finally, the results show that there is a direct correlation between the length of leave taken by the father and his involvement in care afterwards. Overall, these results indicate that the law has had the intended effect of providing children with care from both parents.